Teoreticheskoe i eksperimental'noe obosnovanie tipov adaptatsii v sportivnom ontogeneze lyzhnikov-gonshchikov - Kharitonova, L. G.; Mikhalev, V. I.; Shklyaev, Yu. B. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
The aim of this study to make the theoretical and experimental substantiation of adaptation types at the sports ontogenesis of cross-country skiers. The obtained data allow to define three constitutional types of the cross-country skiers' adaptation: "long-distance", "universal" and "sprinting". Types of adaptation are to be taken into consideration for the selection of gifted athletes, in organizing the complex control and correction of training process at various stages of sports ontogenesis.